Frankie Drake mysteries. The complete second season [videorecording (DVD)] - Smith, Lauren Lee, 1980-; Lil Buck, 1988-; Liddiard, Rebecca (PBS, 2019)
The year is 1921. While communism and prohibition are debated in speakeasies, society will never be the same, and crime has never had it better. A new age calls for a new kind of detective and the women of Drake Private Detectives fit the bill.